2012
DOI: 10.3350/cmh.2012.18.4.368
|View full text |Cite
|
Sign up to set email alerts
|

Clinical outcomes of balloon-occluded retrograde transvenous obliteration for the treatment of gastric variceal hemorrhage in Korean patients with liver cirrhosis: a retrospective multicenter study

Abstract: Background/AimsThis study evaluated the clinical outcomes of balloon-occluded retrograde transvenous obliteration (BRTO) for the treatment of hemorrhage from gastric varices (GV) in Korean patients with liver cirrhosis (LC).MethodsWe retrospectively analyzed data from 183 LC patients who underwent BRTO for GV bleeding in 6 university-based hospitals between January 2001 and December 2010.ResultsOf the 183 enrolled patients, 49 patients had Child-Pugh (CP) class A LC, 105 had CP class B, and 30 had CP class C a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
32
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(35 citation statements)
references
References 23 publications
2
32
1
Order By: Relevance
“…Moreover, the spontaneous portal-systemic shunt (mainly the GRS) may be reserved ( Figure 5(c)). Therefore, in the present study, although portal vein pressure (PVP) increased from 24.3 (8-47.8 mmHg) to 29.1 (10-48.6 mmHg), the rate at which esophageal varices worsened was only 13%, and this was lower than the rate reported for BRTO (up to 63%, with 11-24% of cases showing subsequent variceal bleeding) [51,52].…”
Section: Discussioncontrasting
confidence: 69%
“…Moreover, the spontaneous portal-systemic shunt (mainly the GRS) may be reserved ( Figure 5(c)). Therefore, in the present study, although portal vein pressure (PVP) increased from 24.3 (8-47.8 mmHg) to 29.1 (10-48.6 mmHg), the rate at which esophageal varices worsened was only 13%, and this was lower than the rate reported for BRTO (up to 63%, with 11-24% of cases showing subsequent variceal bleeding) [51,52].…”
Section: Discussioncontrasting
confidence: 69%
“…Meanwhile, Jang reported that rebleeding from gastrointestinal tracts after B-RTO occurred in 30 patients (22%) undergoing treatment of gastric variceal hemorrhage during an average follow-up of 36.0 months. The authors estimated the rebleeding-free rate at one, three and five years to be 87.5%, 74.8% and 68.9%, respectively (12). Using our technique, no patients experienced bleeding or recurrence of the GVs after the B-RTO and simultaneous EIS procedure during an average followup duration of 38.3 months.…”
Section: Discussionmentioning
confidence: 84%
“…For example, Jang reported that EV newly developed in 21 of 36 (58.3%) patients without EV prior to B-RTO, while EV increased in size in 33 of 100 (33%) patients with EV prior to B-RTO (12), and Tanihata reported that EV newly developed in three of 19 patients (15.8%) without EV prior to B-RTO, whereas EV increased in size in eight of 19 (42.1%) patients with EV prior to B-RTO (13). In contrast, in our series, no cases of EV newly developed among seven patients without EV prior to B-RTO, indicating that our procedure is potentially superior to B-RTO alone with respect to the lower risk of new EV development.…”
Section: Discussionmentioning
confidence: 99%
“…TIPS insertion appears effective for the prevention of gastric variceal rebleeding, although it is more invasive than endoscopic methods, has associated risks of encephalopathy and is not always available [22,30,37] . BRTO: A retrospective study performed by Jang evaluated the clinical outcomes of BRTO for the management of gastric variceal hemorrhage [38] . In 183 patents with confirmed gastric variceal bleeding, BRTO was performed with a technical success of 96.7%, and procedure-related complications occurred in 4.4%.…”
Section: Radiologic Therapies Tips: Tripathi Described Tips Placementmentioning
confidence: 99%